Development of a Clinical-Based Academic Supervision Model for Islamic Religious Education and Character Education Teachers in Senior High Schools in West Sumatra Province - Erwanto, Erwanto (Ruhama : Islamic Education Journal, 2023)
The central issue addressed in this research is the lack of effectiveness and comprehensiveness in the implementation of academic supervision by Islamic Religious Education (PAI) supervisors in high schools in West Sumatra Province. This situation has implications for the performance of some PAI teachers in delivering quality and dynamic education towards professionalism. The objectives of this study are: (1) to develop a clinical-based academic supervision model for Islamic Religious Education and Character Education teachers in high schools in West Sumatra Province, and (2) to test the validity, effectiveness, and practicality of the developed clinical-based academic supervision model in these subjects. This research employed the Research and Development (RD) methodology, following the model developed by Sivasailam Thiagarajan. The development procedure followed the 4-D stages. Data analysis involved both qualitative and quantitative techniques. The research successfully developed a clinical-based academic supervision model for Islamic Religious Education and Character Education teachers in high schools in West Sumatra Province. The test results of the model, including validity, effectiveness, and practicality assessments, indicated that the model is valid, effective, and practical for implementation.